Plea Bargaining In The 2025 Draft Indonesian Criminal Procedure Code: Legal Certainty And Justice - Dedi Wardana Nasoetion; Noenik Soekorini; Hartoyo Hartoyo (Fakultas Hukum Dehasen, 2025)
The enactment of Law No. 20 of 2025 on the Indonesian Criminal Procedure Code (KUHAP) introduces plea bargaining as a negotiated mechanism permitting admissions of guilt in exchange for sentencing concessions, marking a paradigmatic shift from judicial truth-seeking toward prosecutorial negotiation. This study examines whether such a shift is constitutionally coherent within Indonesia’s civil law framework. Using a normative juridical (doctrinal) methodology grounded in hierarchical norm theory, constitutional interpretation, and principled balancing, the research analyzes the compatibility of plea bargaining with legal certainty, equality before the law, presumption of innocence, and rule-of-law principles under UUD 1945. The findings demonstrate that while plea bargaining is formally valid within the statutory hierarchy, its substantive legitimacy is conditional. Ambiguities in eligibility criteria and sentencing parameters risk undermining legal certainty; expanded prosecutorial discretion raises equality concerns; and significant sentencing differentials may threaten voluntariness. Judicial oversight emerges as the decisive safeguard, requiring substantive verification of voluntariness, evidentiary sufficiency, and proportionality. The study concludes that plea bargaining is normatively defensible only if reinforced by strict judicial control and clearly structured procedural safeguards. This research contributes an integrated constitutional-doctrinal framework clarifying the legitimacy conditions of negotiated justice within civil law systems.